Families in venture capital - Pelucco, Valerio (Strategic Management Journal, 2026)
Abstract Research Summary This exploratory paper introduces a new type of family business by studying the investment strategies of family‐managed venture capital funds (“Family VCs”) across a multi‐country setting. It shows that Family VCs are more likely to invest in (syndicate with) geographically proximate startups (investors), indicating a preference for local investments. This tendency is stronger when the VC is named after the family and the family is closely involved in the decision‐making process of the fund. I provide suggestive evidence that this pattern reflects both superior local knowledge (rational response) and home bias (non‐rational response), with the latter becoming more pronounced when performance pressure is lower. Managerial Summary Family‐managed VC funds (Family VCs), managing roughly $29 billion, represent an important segment of the venture capital industry. I show that family control shapes both the selection of startups and syndicate partners. Family VCs are indeed more likely to support ventures and partner with investors from their communities, particularly when family members are highly involved in investment decisions and the fund is named after the family. I provide suggestive evidence that this local preference stems from both rational factors, like superior local knowledge and networks, and a non‐rational preference for local investments. Their local focus becomes relatively less pronounced when families must demonstrate strong financial performance, such as when a follow‐on fund has not yet been raised and during competitive market conditions.